Pertimbangan Hakim Atas Permohonan Dispensasi Nikah (Studi Kasus Atas Penetapan No : 27/Pdt.P/2024 PN Tarutung) - Roma Cita Sibatuara; Debora (Universitas Muhammadiyah Kotabumi, 2024)
Abstract This study looks at the factors that judges in the Tarutung District Court take into account when approving applications for marriage dispensation. Law Number 16 of 2019's Article 7 Paragraph 1 serves as the study's legal foundation. According to the study's findings, the desire to avoid adultery and extramarital pregnancy were the primary reasons for marriage dispensation cases in this court. In reaching their decision, the judges took into account the principles of benefit, child and fetus interests, and adherence to family law.In light of these results, it is advised that the government and environmental groups step up their efforts to raise awareness of the dangers of child marriage and provide counseling, all the while bolstering parental and family monitoring of children's social development. Keywords: dispensation; judge’s consideration; marriage Abstrak Penelitian ini meneliti kriteria yang menjadi pertimbangan hakim Pengadilan Negeri Tarutung dalam mengabulkan permohonan dispensasi nikah. Pengumpulan data dilakukan melalui wawancara dan observasi secara kualitatif. Landasan hukum dalam penelitian ini adalah Pasal 7 Ayat 1 Undang-Undang Nomor 16 Tahun 2019. Berdasarkan hasil temuan penelitian, penyebab utama gugatan dispensasi nikah di pengadilan ini adalah kehamilan di luar nikah dan mneghindari perzinaan. Hakim dalam memutus perkara ini mempertimbangkan ketaatan hukum keluarga, kepentingan anak dan janin, serta asas kemanfaatan. Mengingat adanya temuan ini, maka disarankan agar pemerintah dan organisasi lingkungan meningkatkan upaya mereka untuk mempromosikan risiko pernikahan dini dan menawarkan konseling, sekaligus memperkuat pengawasan keluarga dan orang tua terhadap perkembangan sosial anak. Kata kunci: dispensasi; pertimbangan hakim; pernikahan.